Coeliac disease – is a small intestinal biopsy always necessary for diagnosis?. (24th May 2012) - Whyte, LA; Humphries, L; Tuthill, DP; Davies, IH; Jenkins, HR
Abstract : Introduction: Increasing numbers of children with coeliac disease (CD) have minor gastrointestinal symptoms (GI) or are diagnosed following screening of asymptomatic children in high risk groups. The diagnosis of CD is changing, and it is suggested that with improved accuracy of blood antibody testing, intestinal biopsy may not always be necessary. Methods: We reviewed all patients with CD presenting to a regional centre between 2005-10 and compared the mode of presentation with previous data from the same area (1983-2004). In addition we reviewed the last 100 cases of proven CD to assess the accuracy of antibody testing. Results: Median age at diagnosis was 13 years, compared with 8 years 1999-2004. 41% presented with specific GI symptoms, 23% with non-GI features and 36% were diagnosed after screening of high risk groups. Compared with previous studies from the same population, percentage of patients presenting with GI symptoms remained similar (42% v 41%) but patients diagnosed after targeted screening had increased (26% to 36%). Of the last 100 patients with a histological diagnosis of CD, IgA anti-TTG antibody levels (normal 0-10) were >200 in 12%, between 100 and 200 in 22%, between 50 and 100 in 57%, between 30 and 50 in 9%. All patients with a TTG level > 48 showed sub-total villous atrophy on small intestinal histology. Conclusion: The frequency and median age at diagnosis of CD has continued to rise. Over 50% of patients presented with few or no symptoms. Current antibody testing appears to be accurate enough in our centre to suggest that histological confirmation may not be necessary to make a diagnosis in all cases.